Main factors of Kota Kinabalu residents tend to use the private vehicle - Siti Nurmasyittah Ag Besar; Mohd Azizul Ladin; Noor Sheena Herayati Harith; Nurmin Bolong; Ismail Saad; Nazaruddin Abdul Taha (Academia Industry Networks, 2021)
Kota Kinabalu is the capital city of Sabah which acts as economic and administration centre and fondly known as KK. The migration of people due to wide opportunities has enhanced the population growth drastically. Unexpectedly, this led to the increase of the travel demand. This has been proven as the number of vehicles travelling in and out of the city grows by 8.3% annually by the number of roads grows at a slower rate, causing worst traffic congestion mainly during peak hours. Hence, this study has been conducted in order to determine the relationship between variables and car ownership in Kota Kinabalu, the relationship between variables with the type of vehicles use for travelling in Kota Kinabalu City as well as to study the factor of Kota Kinabalu residents tend to use the private vehicles in Kota Kinabalu City. An online survey being conducted via Google Form to obtain the findings and chi-square test has been done to analyse the data. It is found that the most factors that encourage people to use private vehicles in Kota Kinabalu City are security concerns, hygiene as well as the time and destinations flexibility.